The determination of stage in nonmuscle urothelial carcinoma: Staining pattern of caspase-8 - Nilay Şen Türk; Saadettin Eskiçorapçi; Zafer Aybek; Levent Tuncay (Wolters Kluwer Medknow Publications, 2018)
Context: Urothelial carcinoma (UC) is one of the most frequent epithelial tumors worldwide. Aims: We aimed to investigate the protein expressions of caspase-8, p53, murine double minute 2 (mdm2), and p14ARF in nonmuscle UCs and to correlate the findings with clinicopathological characteristics. Settings and Design: A total of 50 patients who had pTa and pT1 tumors were analyzed. Subjects and Methods: The protein expressions of caspase-8, p53, mdm2, and p14ARF were analyzed by immunohistochemistry. Statistical Analysis Used: Chi-square test was done using SPSS version 16.0 (SPSS, Inc., Chicago, IL, USA). Results: Cytoplasmic caspase-8 expression was significantly higher in pT1 UCs while nuclear caspase-8 expression was significantly higher in pTa UCs (P = 0.005 and P = 0.011, respectively). Cytoplasmic caspase-8 expression was also higher in high-grade UCs (P = 0.035). The expression of p53, mdm2, and p14ARF was not also related with pathological stage or grade (P > 0.05 for all). The p14ARF expression was related with nuclear caspase-8 expression in most of the patients. Complete agreement among nonmuscle UCs for immunohistochemical expression of p14 and nuclear caspase-8 was seen in 41 cases, and the pairwise kappa agreement value was substantial (κ =0.614). The patients who had recurrence were positive for both p53 and mdm2 or either p53 or mdm2 (P = 0.025). Conclusions: These results suggested that the staining pattern of caspase-8 might be helpful for determining of the stages in nonmuscle UC. It was also showed that the expression status of p53 and mdm2 were related with the recurrence.